Herpesvirus Infections of the Central Nervous System - Bharucha, Tehmina; Houlihan, Catherine F.; Breuer, Judith (Seminars in Neurology, 2019)
There are over 200 herpesvirus species, of which 10 affect humans. Each of these 10 herpesviruses has a unique clinical syndrome, but common to all is their ability to cause infection and pathology in the central nervous system. In this article, we discuss the epidemiology, clinical presentation, diagnostic modalities, treatment, sequelae, and availability of vaccination of each of the following herpesviruses: herpes simplex virus 1 and 2, varicella zoster virus, human cytomegalovirus, human herpesvirus 6A, 6B, and 7, Epstein–Barr virus, human herpesvirus 8, and simian herpesvirus B.
Keywords: neurological infections; herpesviruses; diagnosis